Classic recipes, tastes and traditions of Indonesia and the Philippines : seasonal dishes from an exotic cuisine, with 150 authentic recipes - Basan, Ghillie; Tan, Terry ; Laus, Vilma (London, 2018)
Indonesia and the archipelago that forms the Philippines border each other, yet have nurtured distinct culinary traditions. Indonesian cuisine has a reliance on fragrant herbs and spices, while in the Philippines the Spanish influence is more evident. The many exciting recipes in this book include Sardines Cooked in Spicy Coconut Milk with Herbs, Colonial Rice Soup with Pork, Filipino Paella, and Adobo, as well as sweet drinks and desserts based on local fruits and coconuts
Keywords: Cooking, Malaysian; Cooking, Philippines